Protective effect of inhaled salbutamol powder in children assessed by histamine challenge. - Pullan, C R (1980)
A double-blind placebo-controlled trial of 100, 400, and 800 micrograms inhaled salbutamol powder was conducted on 12 children. The protective effect at 10 minutes, two hours, and four hours was assessed by histamine challenge. At 10 minutes there was good protection with all doses, but by four hours there was significant protection only with 800 micrograms (p less than 0.01). Salbutamol powder may need to be taken at least every four hours for complete protection. There was a dose-related effect with a single dose of up to 800 micrograms; increasing the dose increased the effect and duration of action. Currently advertised dose regimens of salbutamol powder for children (200 micrograms three or four times a day) are apparently submaximal. Histamine challenge is a satisfactory method of assessing the proective effect of a drug in asthmatic children.